MDM of Hybrid Modes in Multimode Fiber - Angela Amphawan; Yousef Fazea; Mohd Samsu Sajat; Roslinda Murad; Hajar Alias (IAES Indonesia Section, 2015)
This paper reports on MDM of a combination ofhelical-phased modes comprising ring modes and HG modes.44Gbps data transmission is achieved by a wavelength divisionmultiplexing (WDM) - MDM system of two center-launchedhelical-phased ring modes and two 3μm radially offset HG modeon wavelengths 1550.12nm and 1551.72nm for a 1500m-longmultimode fiber. The power coupling coefficients, degeneratemode group delays and bit error rates are analyzed for differentHG modes and radial offsets.